THE ELEVENTH GRADE STUDENTSâ LANGUAGE LEARNING STRATEGIES IN WRITING DESCRIPTIVE PARAGRAPH USING THE PICTURES AT SMA MUHAMMADIYAH 1 PALANGKA RAYA - Arifin, M. Zainal; Utami, Eka Sri (LP2M IAIN Palangka Raya, 2013)
The purpose of this study was to describe how the students wrote descriptive paragraph through language learning strategies by using pictures at SMA Muhammadiyah 1 Palangka Raya.The approach used in this study was qualitative. To collect the data, this study used observation, interview, and documentation technique. The subjects were 12 eleventh grade students of SMA Muhammadiyah I Palangka Raya. They were selected based on the highest and lowest scores.The findings of this study were: first, the language learning strategies used by successful students in writing descriptive paragraph using the pictures were 1) cognitive strategies as in using resources for receiving and sending messages, translating, and taking notes, 2) compensation strategies as in selecting the topic and coining words, and 3) affective strategies as in making positive statements. Second, the language learning strategies used by unsuccessful students in writing descriptive paragraph using the pictures were 1) cognitive strategies as in using resources for receiving and sending messages, translating, taking notes, and summarizing, 2) compensation strategies as in selecting the topic and coining words, 3) affective strategies as in making positive statements, and 4) social strategies as in asking for correction and cooperative with peers.